Democratic legitimacy as a functional of the civil society - Сивуха, Т. В. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2016)
The article is devoted to the analysis of the system of implementation democratic legitimacy in the context of the civil society formation in Ukraine. The relationship between the categories of democracy, civil society, and the legitimacy of political power have been covered and revealed. The matter of the functional purpose of civil society in the focus of integration of the Ukrainian political system to modern models of European democracies have been addressed. Essential characteristics and applied principles of the mechanism of democratic legitimacy in the terms of the post-modern political process have been studied.